Non-Financial Corporate Debt in Advanced Economies, 2010-17 - Antoun de Almeida, Luiza (IMF Working Papers; Working Paper, 2020)
This paper studies the evolution of non-financial corporate debt among publicly listed companies in major advanced economies between 2010 and 2017. Since 2010, firms have started to rely more on corporate bond markets and have used part of their debt to increase their holdings of cash. In our sample of some 5,000 firms, we find substantial differences across countries, industries, firms, and years in leverage and debt maturity, and we also identify time factors that are common drivers of capital structures. Within countries, loosening an index of financial conditions seems to be associated with lengthening debt maturity after controlling for firms' characteristics. Across firms and countries, leveraging and lengthening debt maturity have been greater where economic growth was stronger. Tighter financial conditions are positively associated with an increase in short-term debt financing. Quantile regressions suggest that there is substantial heterogeneity among firms on how they react to macro-financial conditions: large increases in long-term debt financing and large declines in short-term debt financing tend to be driven more by better macroeconomic performance, while large increases in short-term debt financing are more strongly impacted by tighter financial conditions. Since the paper uses data up to 2017, it does not reflect developments that occurred during the coronavirus pandemic. Nonetheless, sensitivity analysis shows that a significant amount of corporate debt, representing more than 5 percent of GDP, could be at risk in some countries, with an adverse spillover to the financial system if financial conditions tighten or economic growth slows down. This suggests that vulnerabilities should be closely monitored and policy action taken if warranted.